2023
DOI: 10.3389/fmolb.2023.980433
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urinary extracellular vesicles as a source of RNA biomarkers for prostate cancer in liquid biopsies

Abstract: Introduction: Extracellular vesicles (EVs) have emerged as a very attractive source of cancer- derived RNA biomarkers for the early detection, prognosis and monitoring of various cancers, including prostate cancer (PC). However, biofluids contain a mixture of EVs released from a variety of tissues and the fraction of total EVs that are derived from PC tissue is not known. Moreover, the optimal biofluid—plasma or urine—that is more suitable for the detection of EV- enclosed RNA biomarkers is not yet clear.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 84 publications
(86 reference statements)
0
16
1
Order By: Relevance
“…The identification of differentially expressed small RNAs holds considerable diagnostic potential, particularly in cancer and cardiovascular diseases [ 6 , 7 , 8 , 9 , 53 ]. A preliminary iteration of the presented program has been utilised in recent publications focusing on the analysis of extracellular vesicle contents, engaging in discussions about the biological interpretations of the results [ 51 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The identification of differentially expressed small RNAs holds considerable diagnostic potential, particularly in cancer and cardiovascular diseases [ 6 , 7 , 8 , 9 , 53 ]. A preliminary iteration of the presented program has been utilised in recent publications focusing on the analysis of extracellular vesicle contents, engaging in discussions about the biological interpretations of the results [ 51 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“… 148 Furthermore, lncRNA-Linc00662, lncRNA-CHASERR, and lncRNA-PCA3 were significantly elevated in the extracellular vesicles isolated from the urine of prostate cancer (PC) patients. 149 Plasma and urinary EVs as a potential sources of RNA biomarkers for prostate cancer in liquid biopsies.…”
Section: Evs As Disease Marker In Diagnostic Applicationmentioning
confidence: 99%
“…It has been observed that the expression level of circular RNA in urine varies across multiple diseases, offering potential opportunities for circular RNA as a novel diagnostic and therapeutic approach. Unlike other sampling methods, urine collection is a noninvasive, painless, and highly convenient technique that enhances the accuracy and effectiveness of early disease diagnosis and treatment [ 10 ]. Urinary cytology test can be used as the gold standard for the diagnosis of bladder cancer, but this method has insufficient cell collection or improper treatment, which may lead to too low a number of cancer cells in the sample, making them difficult to detect and prone to false negatives [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%